"For your Faithful Lord, Life is Changed not Ended": The Roman Catholic Funeral Rite in Flanders and the Paschal Mystery - Goyvaerts, Samuel (Yearbook for ritual and liturgical studies, 2020)
Since Vatican II, the paschal mystery has become the focal point of all liturgy, a development that also has consequences for the Roman Catholic funeral liturgy. Celebrating the funeral in the context of the Eucharist underscores the concept of the paschal mystery very explicitly. Since 2011, a number of factors has led to the funeral liturgy without Eucharist becoming the liturgical norm in Flanders. This paper investigates this shift in light of the funeral liturgy being a memorial of the paschal mystery. It (1) sketches the shift that occurred in the revised funeral rite, (2) presents a detailed study of the new Flemish approach towards the funeral liturgy, using the diocese of Hasselt as an example, and (3) evaluates this new approach to the funeral liturgy, specifically from the perspective of the liturgy as a memorial of the paschal mystery. Finally, some conclusions regarding this case from a liturgical-theological and pastoral point of view are formulated.